Ascorbic acid attenuates ethanol induced apoptotic and oxidative response by blocking the Bax, Bcl2 and Caspase signaling pathways - Shanmugam, Nathiya; Siddharaman, Rajaram; Ekambaram, Manivannan; Rajendran, Ramya; Ramasamy, Yasothai; Balasubramanian, Ashwinidevi (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Research evidence has demonstrated that oxidative stress plays important etiological role in pathogenesis of alcoholic liver disease. The agents having antioxidant property plays a promising therapeutic intervention in ALD. In our present study we investigate the effect of ascorbic acid on ethanol induced liver injury and molecular mechanism of ethanol induced apoptosis. Methods: Wistar albino rats were randomly divided into 4 groups with 6 animals in each group control, ethanol treatment 40% (2ml/100gm), ethanol+ascorbic acid 100mg/kg b.w. intra-gastric gavage, ethanol+silymarin 100mg/kg b.w. intra-gastric gavage for 21 days. Statistical analysis was carried out using one-way ANOVA followed by Tukey multiple comparision test. Results: Ethanol induced hepatotoxicity is evidenced by increased level of liver marker enzymes (AST, ALT, ALP and LDH) and lipid peroxidation whereas the level of antioxidants (SOD, CAT, GSH, VIT C and E) was significantly decreased. Our results are further supported by histopathological examination which shows drastic changes in liver architecture. Hepatic Bax, Bcl-2, Caspase 3 and Caspase 9 proteins expressions were altered. On contrary treatment with ascorbic acid ameliorated the changes induced by ethanol and improved liver architecture. Conclusions: Ascorbic acid as an antioxidant protect the liver from ethanol induced oxidative damage and apoptosis.